Mexico Urbanization Review : Managing Spatial Growth for Productive and Livable Cities in Mexico - Kim, Yoonhee (Washington, DC: World Bank, 2016)
Despite impressive economic growth and increasing prosperity, cities in Mexico do not seem to have fully captured the benefits of urban agglomeration, in part because of rapid and uncoordinated urban growth. Recent expansion of many Mexican cities has been distant, disconnected, and dispersed, driven mainly by large single-use housing developments on the outskirts of cities. The lack of a coordinated approach to urban development has hindered the ability of cities in Mexico to boost economic growth and foster inclusive development. It also has created a fissure between new housing developments and urban services, infrastructure, and access to employment.